Hydrochemical and Isotopic Study of Water Resources in Khan Al-Baghdadi Area, Al- Anbar Province / West of Iraq - Hussien, Sarmad Jamal; Abdulhussein, Firas Mudhafar (Iraqi Journal of Science, 2021)
This hydrochemical study of the surface and groundwater in Khan AL-Baghdadi area, western Iraq, included the interpretation of physical, chemical, and biological properties. Water samples were collected from wells (14 samples) and surface water of Euphrates River (6 samples) for the dry and wet periods of October 2018 and April 2019, respectively. The stable isotopes analysis was performed for the dry period only. The surface water samples were characterized by slightly alkaline, fresh, excessively mineralized, Ca-chloride type, and hard to very hard water class. While the groundwater samples were characterized by slightly alkaline, brackish, excessively mineralized, Ca-chloride and Na-Chloride type, and hard to very hard water class. The stable isotopic analysis was used in studying the interaction between water resources of Euphrates River and groundwater. Stable isotopes (Î´D and Î´18O) were used to study the hydrological aspects of water resources in the study area. The results showed that surface and groundwater samples have similar source with a correlation relationship between them, in addition to the clear effect of river recharge on groundwater. The variation in Î´2H and Î´18O signature of groundwater in the study area is caused mainly by variation in isotopic composition of recharge water zone and mixing water. Using the Î´ 2H and Î´ 18O diagram, all surface and groundwater samples were plotted below the global meteoric water line (GMWL) and Local Meteoric Water line (LMWL), indicating the influences of the evaporation processes and seasonal variation.